Situated cognition, dynamic systems and art - Brinck, Ingar ; 0000-0002-1299-7878 (Janus Head, 2007)
It is argued that the theory of situated cognition together with dynamic systems theory can explain the core of artistic practice and aesthetic experience, and furthermore paves the way for an account of how artist and audience can meet via the artist’s work. The production and consumption of art is an embodied practice, firmly based in perception and action, and supported by features of the local, agent-centered and global, socio-cultural contexts. Artistic creativity and aesthetic experience equally result from the dynamic interplay between agent and context, allowing for artist and viewer to relate to the artist’s work in similar ways.
Keywords: Arts; aestethic experience; embodied aesthetics; distributed cognition; situated cognition; neuroaesthetics; phenomenology; dynamic systems; Artistic methods; embedded cognition